Association of Dietary Fructose With Serum Advanced Glycation End Products in a Controlled Feeding Study of Healthy Adults. (7th June 2021) - Weigand, Bethany; Palma-Duran, Susana A.; Sweazea, Karen; Lee, Chong; Tasevska, Natasha
Abstract: Objectives: Sugars form advanced glycation end products (AGEs) through natural metabolism and interactions with proteins, lipids, and nucleic acids, which accumulate in tissues and have been implicated in the etiology of chronic diseases. Due to the increased consumption of fructose and its high ability to form AGEs, a further understanding of this association is important to clarify the role of sugars in disease. Our objective was to explore the association between usual fructose intake and serum levels of AGEs in healthy adults. Methods: This is a secondary analysis of a 15-d controlled feeding study ( n  = 100) consuming their usual diet conducted in the Phoenix metropolitan area. Participants completed two 7-d food diaries, and custom 15-d menu plans were created to replicate their habitual diet. Forty participants (mean age: 42.5y, BMI: 27.8, gender: 55% male) were selected based on their 15-d mean total fructose intake for this analysis [top and bottom 20% of the sample distribution; high fructose (HF) =20 (76.3 ± 12.5 g/day), low fructose (LF) = 20 (27.3 ± 5.4 g/day)]. Fasting serum collected five weeks after the feeding period were analyzed for carboxymethyl-lysine (CML), a major AGE, using ELISA kits. A database of 549 common foods with known CML amounts was used to calculate exogenous CML intake. A general linear model was fitted to investigate the difference in serum CML between LF and HF groups while adjusting for age, gender, BMI, and exogenous CML intake. Results: Exogenous CML intake was not significantly different between the HF and LF groups ( P  = 0.925). Participants in the HF group had significantly higher serum CML levels compared to participants in the LF group (37.3 ± 8.4 ng/mL versus 30.5 ± 8.0 ng/mL; P  = 0.013). This difference remained statistically significant after adjusting for covariates [LF vs. HF: β = −6.4 (SE = 2.9); P  = 0.036; Log10(age): β = −12.0 (10.6), P  = 0.267; BMI: β = 0.4 (0.4), P  = 0.352), male vs. female: β = 1.2 (3.6), P  = 0.753; and exogenous CML intake: β = −8.5 (10.2), P  = 0.411]. Conclusions: Our findings suggest that endogenous CML formation may be an explanation for the significant difference in serum CML between HF and LF groups. This is significant in further understanding mechanisms of sugar intake and disease etiology and could have implications for at-risk populations consuming a high fructose diet. Funding Sources: NIH/NCI and ASU